Resepsi Hadis dalam Sinetron Taqdir Ilahi: Ujian dari Allah - Wijayanti, Sherina (Al-Qudwah, 2023)
This research discusses a movie titled “Taqdir Ilahi Ujian dari Allah” whose content is from Prophet Muhammad PBUH hadith. This article tries to photograph the role of hadith meditation which is presented in religious movies, where the religious proselytizing of hadith through the movie attracts the society to reconsider the hadith until the functional which is illustrated by the actors and actresses involved. The development of technology takes place transforming hadith into a form of a movie as its development, however, on the other side, it becomes harder challenging when the hadith is only visualized textually. At this point, the hadith formed into a movie has not been entirely respresenting the reality of sequences there. It’s not without cause, this happens because the divergence between the reality of people in the past to this era is inapplicable. The movie presents the delivering of Prophet PBUH hadith effectively through the scenes with actually with the chronological background in Indonesia Archipelago. The purpose of this study is to provide the occurrence of digital hadith which has shaped into the visual domain presented in the form of religious movies. The research uses the qualitative method by directly having the observation through watching the movie titled “Taqdir Ilahi Ujian dari Allah” as the primary source, then together with this, the library study is used as the secondary source which correlates to this research. This research shows first, the scenes illustrate hadith tangibly by the actors and actresses so that the society can take the wisdom. Second, the movie “Taqdir Ilahi Ujian dari Allah” reflects hadith through exegetical, aesthetic, and functional. Third, even though the movie has tried to present hadith’s, it still does not reflect the hadith entirely, but it can become the alternative for society to understand hadith easily.  Abstrak: Kajian ini membahas Sinetron Taqdir Ilahi_Ujian dari Allah yang subtansinya bersumber dari sabda Nabi Muhammad SAW. Artikel ini berupaya memotret model mediatisasi hadis yang dikemas dalam bentuk sinetron religi, dimana penyajian dakwah hadis melalui sinetron menarik masyarakat untuk meresepsi hadis sampai tahap fungsional dengan diperagakan oleh para aktris dan aktor yang terlibat. Kemajuan teknologi turut mentransformasi hadis ke ranah mediatisasi sinetron sebagai kemajuan, namun disisi lain menjadi tantangan yang lebih berat ketika hadis tervisualisasi hanya secara tekstual. Pada titik  ini, mediatisasi hadis berupa sinetron belum sepenuhnya dapat mewakili realitas kronologis yang ada. Bukan tanpa sebab, hal ini dikarenakan kesenjangan realitas masyarakat masa dulu dengan masa kini yang tidak relevan. Potret sabda Nabi Muhammad SAW yang dikisahkan dalam sinetron disampaikan secara praktis, melalui adegan-adegan yang diperagakan secara aktual dengan latar kronologis Nusantara. Tujuan penelitian untuk menyajikan fenomenologi digital hadis yang sudah sampai ranah visual dengan dikemas dalam sinetron religi. Penelitian ini menggunakan metode kualitatif dengan observasi langsung dalam menyaksikan film sinetron “Taqdir Ilahi_Ujian dari Allah” sebagai sumber primer, serta menggunakan pendekatan studi pustaka sebagai sumber sekunder terkait topik yang berkaitan dengan penelitian ini. Penelitian ini menghasilkan pertama, adegan yang diperankan para pemain sinetron mengilustrasikan hadis secara konkrit sehingga dapat diambil hikmahnya oleh masyarakat luas. Kedua, sinetron “Taqdir Ilahi_Ujian dari Allah” meresepsi hadis secara eksegesis, estetis dan fungsional. Ketiga, hadis yang dikemas berupa sinetron tidak sepenuhnya mewakili realitas pada hadis, namun cukup menjadi alternatif bagi masyarakat untuk memahami hadis secara praktis.